Pemanfaatan Wodershare Filmora Dalam Meningkatkan Kemampuan Sumber Daya Manusia Di Dinas Sosial Provinsi Sumatera Selatan - Hartati, Ery; Ricoida, Desy Iba; Fransen, Lisa Amelia (FORDICATE, 2021)
Lack of skills in the ability to edit videos and has become anobstacle for the Human Resources department at the Social Service ofSouth Sumatra Province in presenting information that is attractiveand interesting to the public. Therefore, training in the use ofWodershare Filmora software is needed to improve the skills of theHuman Resources department in video editing. From the trainingprovided, it was seen that the participants were enthusiastic inparticipating and practicing directly the software used and increasingtheir understanding of using the Wodershare Filmora software. It ishoped that in the future the training can be carried out on a scheduledbasis so that the material presented can be more in-depth and theability of the trainees to increase.